2021
DOI: 10.1039/d0fd00010h
|View full text |Cite
|
Sign up to set email alerts
|

Capturing spatially resolved kinetic data and coking of Ga–Pt supported catalytically active liquid metal solutions during propane dehydrogenationin situ

Abstract: Supported liquid phase catalysis has great potential to unify the advantages from both, homogeneous and heterogeneous catalysis. Recently, we reported Supported Catalytically Active Liquid Metal Solutions (SCALMS) as a new...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 48 publications
3
38
0
Order By: Relevance
“…As mentioned above, the ability of oxidic Ga to catalyze alkane dehydrogenation has been already reported, and the presence of Ga δ+ species on the surface of the passivated gallium droplets may be held responsible for the observed catalytic activity. Conversely to the SCALMS system, Ga oxide cannot be fully reduced in the absence of H 2 ‐activating metal atoms (such as Pt in the case of Ga 52 Pt/SiO 2 ) . The dehydrogenation activity of gallium oxide is accompanied by a significant tendency to promote by‐product formation, via cracking and/or isomerization reactions.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned above, the ability of oxidic Ga to catalyze alkane dehydrogenation has been already reported, and the presence of Ga δ+ species on the surface of the passivated gallium droplets may be held responsible for the observed catalytic activity. Conversely to the SCALMS system, Ga oxide cannot be fully reduced in the absence of H 2 ‐activating metal atoms (such as Pt in the case of Ga 52 Pt/SiO 2 ) . The dehydrogenation activity of gallium oxide is accompanied by a significant tendency to promote by‐product formation, via cracking and/or isomerization reactions.…”
Section: Figurementioning
confidence: 99%
“…After the preparation of catalysts via calcination, it can be assumed that Ga is present as bulk Ga 0 droplets coated with a thin passivation layer of Ga 2 O 3 which is known to be an active alkane dehydrogenation catalyst itself but leads also to the formation of cracking products . For a material such as Ga 52 Pt/SiO 2 SCALMS, the presence of a hydrogen‐activating metal enables the reduction of the oxidic passivation layer under hydrogen atmosphere at 450 °C . Hence, we exposed Ga 52 Pt/SiO 2 SCALMS to a hydrogen pretreatment at 450 °C before MCH dehydrogenation reaction.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Under dehydrogenation conditions (>623 K) the Ga/noble metal phase is present as a homogeneous liquid [47]. Diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS), with CO as a probe molecule, has been applied to Ga/Al Spatially resolved kinetic data were acquired during PDH over GaPt/SiO 2 SCALMS [48]. The results showed an enhanced deactivation of the catalyst at the end of the bed, with the deactivation front moving from the end to the beginning of the catalyst bed over the time on stream, probably due to the enhanced coking of the catalyst under high conversion.…”
Section: Supported Liquid Metal Solutionsmentioning
confidence: 99%
“…In particular, the Pd-Ga system is very well studied since Ga is characterized by its low melting point (29.7 • C) [12] and is also known to dissolve most transition metals [13]. Furthermore, it has been reported that the distinctive surface texture of Pd-Ga causes the excellent catalytic performance of this type of material [14], although other material compositions, such as Pt-Ga [15,16] or Rh-Ga [10], are promising alternatives. The abovementioned catalyst systems exhibit complex threedimensional (3D) structures which govern the catalyst properties [17].…”
Section: Introductionmentioning
confidence: 99%